Analysis of Wireless Network Quality at Muhammadiyah Vocational School Rembang Using QOS (Quality of Service) Parameters - Saputra, Crisna Dwiki; Wijayanto; Ade Ricky Rozaqqi (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze the quality of the wireless network at SMK Muhammadiyah Rembang using the Quality of Service (QoS) parameters, which include throughput, delay, jitter, and packet loss. Data collection was carried out through direct measurement using the Wireshark application on the wireless network in the laboratory room. The collected data were then analyzed based on the TIPHON standard to determine the network quality level. The results of the study during both learning activities and break time indicate that the average throughput falls into the good category, delay is in the excellent category, jitter is in the good category, and packet loss is within the recommended limits. Overall, the wireless network quality at SMK Muhammadiyah Rembang is adequate to support information technology–based learning activities.